ANALISIS MANAJEMEN RISIKO DALAM PROYEK SPALD-T: STUDI KASUS DI DKI JAKARTA: ANALISIS MANAJEMEN RISIKO DALAM PROYEK SPALD-T: STUDI KASUS DI DKI JAKARTA - Nining Ardiyanti Hasan; Acep Hidayat; Mawardi Amin (Jurnal Pensil : Pendidikan Teknik Sipil, 2025)
The Centralized Domestic Wastewater Management System (SPALD-T) projects play a crucial role in improving urban sanitation but face various risks that can affect project performance. This study aims to analyze the influence of risk factors on SPALD-T project performance in DKI Jakarta. Using a quantitative approach with a cross-sectional design, data were collected through a survey of 125 members of the SPALD-T project team. The questionnaire used has undergone validity and reliability tests to ensure accurate measurement of variables. Multiple regression analysis was employed to test the relationship between risk factors and project performance. The results indicate that waste management risk has a significant and positive influence on project performance, with a regression coefficient of 0.188 and a p-value of 0.001. Meanwhile, technical risk shows a positive trend but is not statistically significant, with a regression coefficient of 0.104 and a p-value of 0.078. These findings emphasize the importance of a comprehensive risk management approach, especially in waste management aspects, to improve SPALD-T project performance. This research contributes to the development of more effective risk mitigation strategies in the context of sanitation infrastructure projects in Indonesia and highlights the need for further research on the interaction between various types of risks in influencing project performance.